?STUDIES FOR HETEROSIS AND COMBINING ABILITY IN RICE - ALI, SYED SULTANAL; KHAN, MUHAMMAD GHAYYUR (Biological Sciences - PJSIR, 1995)
A 4 x 4 diallel cross experiment was conducted to estimate the manifestation of heterosis, heterobeltosis and combining ability for plant height, number of tillers per plant,panicle length number.of spikeletsper panicle, number of grains per panicle, percentage filled spikelet density, panicle weight and grain yield per plant. The magnitude of positiveandsignificantheterosiswasquitehighinallthecharactersexceptplantheight,percentagefilledspikeletsand spikelet density.As regard heterobeltosis, number of tillers per plant, panicle weight andgrain yield perplant showed significant positive valuesover thebetter parent in mostofthecrosses.Awiderange of variation was noted for all the nine characters for general and specificcombining abilities.Non-additivegene actions wereobserved for all the traits except plant height and panicle length, for which only additivegene effectwere important.The mean varietal perfor- mance was linearly related to GCA values for grain yield and yield components. Basmati 385 proved to be a good general combiner for most of the traits. Based on mean performance coupled with SCAeffects of the crosses and varietal GCAeffects,crosses Basmati 370X Basmati385,4048 XBasmati 198andBasmati 370x Basmati 198could be recommended for pure line development.